UJI EFEKTIFITAS UNSUR MAGNESIUM DALAM PUPUK DAUN TERHADAP SERANGAN PENYAKIT TIKKA DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) - Santosa, Sartono Joko; Triyono, Kharis - (Joglo)
ABSTRACT The research was aimed to know the effective of Magnesium in foliar fertilizer to over come the attack of tikka disease on groundhut. The method was arranged in Randomized Completely Block Design (RCBD) done on regosol type of soil. The groundnut of â€œGajahâ€ variety was treated by Supermes plus 0,5% magnesium, Supermes plus 1% magnesium, Supermes plus 1,5% magnesium, Gandasil, and Tress. Each treatment was replicated three times and in each treatment, ten samples were picked up. The significant data were analyzed with Duncanâ€™s Multiple Range Test 5%. The research indicates that foliar fertilizer application showed significant effect to the intensity of tikka disease, the number of filled pods, the weight of filled pods, the number of empty pods, the fresh weight of biomass and the dry weight of biomass. Supermes plus 1% of Mg shows the lowest intensity of tikka disease (30% on 45 days after sowing and 34 % on 66 days after sowing). It leads to being able to provide the best growth on the dry weight of biomass of 15,887 g and the highest on weight of filled pods of 20,801 g. Key words : Magnesium, foliar fertilizer, tikka disease, groundnut